Semiconductor optoelectronic devices : introduction to physics and simulation - Piprek, Joachim (Academic Press, 2003)
This book builds a much needed bridge between theoretical and experimental research in optoelectronics by providing both fundamental knowledge in semiconductor physics and real-world simulation examples.